Archaeological, Ethnohistorical, and Ethnobotanical Records of Potatoes in the Andes Mountains - López Estupiñán, Laura (Universidad Pedagógica y Tecnológica de Colombia, 2023)
The potato is a food that allows us to understand the settlement process and the development of complex societies in America. The archaeological, ethnohistorical, and ethnobotanical evidence compiled for this article shows the presence and manipulation of solanum sp. over 13,000 years ago. This includes archaeological findings related to potatoes from micro- and macro-remains, as well as representations that are part of museum collections. We illustrate the description, production, and uses of potatoes in two production centres in South America during the colonial era: the Cundiboyacense highlands in the northern Andes and Huarochiri in the central Andes. Finally, we explore the uses, meanings, and forms of production of native potatoes from the Andean worldview. As a result, we find a great diversity of potatoes that give an account of cultural changes in the uses, conceptions, practices, and management since pre-Hispanic times, leading to worldwide potato consumption and production.